1994
DOI: 10.1002/art.1780370510
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid factor, HLA–DR4, and allelic variants of DRB1 in women with recent‐onset rheumatoid arthritis

Abstract: Objective. To examine the relationship of rheumatoid factor (RF) to HLA-DR4 and alleles of DRBl in women with recent-onset rheumatoid arthritis (RA).Methods. Incident cases of RA were identified as part of a prospective, population-based cas-ontrol study. HLA typing was completed for 246 cases meeting criteria for definite or classic RA.Results. One hundred thirty-six patients (55%) were positive for DR4, and 130 (53%) were RF positive. DR4 was found to be strongly associated with seropositivity (odds ratio 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 27 publications
0
8
1
1
Order By: Relevance
“…While some investigators have claimed a significant diseasemodifying influence of DR4, in that DR4-positive patients were shown to develop a higher degree of destructive joint disease than DR4-negative patients (10,(19)(20)(21), other investigators could not confirm such a relationship (22,23). Similarly, the association between HLA markers and seropositivity or the presence of nodular disease remains controversial (24)(25)(26). In addition to the association of particular clinical presentations with HLA, a gene-dose effect was appreciated for DR4 and the presence of the shared epitope, since patients homozygous for these markers more often exhibited systemic manifestations such as Felty's syndrome and extraarticular organ involvement (27).…”
mentioning
confidence: 99%
“…While some investigators have claimed a significant diseasemodifying influence of DR4, in that DR4-positive patients were shown to develop a higher degree of destructive joint disease than DR4-negative patients (10,(19)(20)(21), other investigators could not confirm such a relationship (22,23). Similarly, the association between HLA markers and seropositivity or the presence of nodular disease remains controversial (24)(25)(26). In addition to the association of particular clinical presentations with HLA, a gene-dose effect was appreciated for DR4 and the presence of the shared epitope, since patients homozygous for these markers more often exhibited systemic manifestations such as Felty's syndrome and extraarticular organ involvement (27).…”
mentioning
confidence: 99%
“…In one study, the highest disease penetrance occurred with genotypes *0401 and *0404/*0102 for males, but with *0401/*0401 for females 81 . In Caucasians, RF is positively linked with DRB1*04 SE‐containing alleles 61,63 and negatively linked with DRB1*01 SE‐containing alleles 67,82 . An association with nodules, which are uncommon in seronegative patients, is less clear.…”
Section: Genetic Markersmentioning
confidence: 99%
“…Many studies have evaluated whether certain HLA types are more frequent in seropositive versus seronegative patients. Several have shown that HLA-DR4 is strongly associated with seropositive RA (56)(57)(58)(59)(60)(61)(62). Ploski et al (58) noted that certain subtypes, particularly DRB1*0401 and DRB1*0408, were associated with what was described as "clearly seropositive disease."…”
Section: Immunogeneticsmentioning
confidence: 99%